Accelerating Supply Chain Performance: The Crucial Role of Artificial Intelligence Mediation in Driving Adaptability and Collaboration in Indonesia's Automotive Supply Chain - Kurbandi Satpatmantya Budi Rochayata; Wening Ken Widodasih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The purpose of this study is to establish the role of Artificial Intelligence in supporting the supply chain performance of automobile manufacturing companies, at the Bekasi industrial complex. The authors investigate whether Artificial Intelligence is a mediating factor of two independent variables, Adaptability and Collaboration, and the dependent variable, overall supply chain performance. This study applied a quantitative approach and obtained data from 133 respondents of executives of automotive companies on supply chain operations. The SEM model was applied in this study, and validated using Smart PLS. All the hypotheses were verified by the findings. Adaptability and collaboration have direct positive impacts on supply chain performance. This study also verified that Artificial Intelligence is a very strong mediator. Artificial Intelligence is very instrumental in enhancing Adaptability and Collaboration for the purpose of maximizing supply chain performance. In this article, it is implied that firms with good Adaptability and Collaboration frameworks are better positioned to take full advantage of Artificial Intelligence, and Artificial Intelligence functions perfectly in maximizing the salutary effect of Adaptability and Collaboration. Thus, the firms must make use of Artificial Intelligence paramount to maximize their supply chain operations.   Keywords: Supply Chain Adaptability, Supply Chain Collaboration, Artificial Intelligence, Supply Chain performance, Automotive Industry.